How challenges and peers contribute to social-emotional learning in outdoor adventure education programs. (June 2020) - Orson, Carolyn N.; McGovern, Gina; Larson, Reed W.
Abstract: Introduction: Many youth development programs view adolescents' process of grappling with challenges as a major driver of social-emotional learning. Our goal was to understand these processes as experienced and enacted by youth. We focused on the program Outward Bound in the United States because its students experience significant physical and social challenges and it has well-developed staff practices for facilitating learning from challenges. Methods: Group interviews were conducted with 32 youth (ages 14–18; 50% female), immediately following their completion of Outward Bound expedition courses. Students were asked to provide a detailed narrative account of an episode on course in which they learned from challenges. Grounded theory analyses identified three processes that contributed to learning. Results: First, students, described developing skills for persistence through successfully enduring distress and a process of experimenting with new mindsets that helped them rise above their anxiety and distress. Second, we found that peers provided skillful and responsive on-the-spot support that motivated youth, helped them succeed, and scaffolded students' learning strategies for dealing with physical, social, and emotional challenges. Third, we found that this peer support and scaffolding was animated by a culture of compassion and mutual commitment, which was cultivated by staff and embraced by youth. Conclusions: These findings from Outward Bound illuminate a learning model that may be useful to other youth programs. This model combines intense challenges with attuned peer support for adolescents' active processes of addressing and learning from challenges. We highlight program structures and staff practices that support these processes.